Uma etnografia na Comunidade Negra Rural Cerro das Velhas: memória coletiva, ancestralidade escrava e território como elementos de sua auto-identificação quilombola. - Haerter, Leandro (2010)
The main point of this dissertation is the quilombola self-identification process lived through the Rural Black Community of Cerro das Velhas, located on Armanda, 5th District of Canguçu, in Brazil. By the ethnography method, it can be pointed out their collective memory and historical documents connected to the old ladies who were slaves owners that originated this collective, since a leaving of lands. The slave heritage, the strategies to accomplish the territories and collective memory are elements that contribute to the black people of this community self-identification as quilombolas . From this problematic of self-identification as quilombola to this specific rural black community, the following questions may appear: from the assumption that social identify is redefined as quilombola , which are the identification markers that contribute to the process of self-identification and which are the peasant s reproduction strategies/territorialization of the mentioned community that benefit the people s self-identification as quilombolas , recognizing the social network and the external mediators. Thereby, the ethnographic text develops itself presenting data about the collective memory, identity, territory strategies of the Associação Quilombola Cerro das Velhas on the elaboration of quilombola self-identification, dynamic and relational process.